UMPSA received a courtesy call from The Honourable Senator Isaiah D Jacob, Member of the National Assembly of Parliament - Nurul Izzah, Abu Bakar (UMPSA, 2024)
PEKAN, 18 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently received a courtesy visit from a Member of the National Assembly of the Parliament of Malaysia, The Honourable Senator Isaiah D Jacob, to inspect the facilities for the persons with disabilities and to see for himself the initiative and the contribution of the university in the effort to achieve inclusivity in order to accommodate the persons with disabilities of UMPSA as well as the surrounding community.